Fountain of youth: The impact of nostalgia on youthfulness and implications for health. Issue 3 (3rd May 2016) - Abeyta, Andrew A.; Routledge, Clay
Abstract: The present research explored the impact of nostalgia on feelings of youthfulness, as well as the health benefits of nostalgia-induced youthfulness. Previous research indicates that feeling younger than one's current age has positive implications for health. We predicted that, relative to ordinary autobiographical memories, nostalgic memories would make people feel more youthful. Further, we predicted that feelings of youthfulness would in turn lead to more positive attitudes about health and physical ability. Studies 1 and 2 demonstrated that, as people get older, nostalgic reverie relative to a control makes them feel more youthful. In Study 3, adults 40 and older who recalled a nostalgic memory from high school reported feeling more youthful than those who recalled an ordinary high school memory. Nostalgia-induced youthfulness in turn predicted the extent to which participants felt healthy, confident about their physical abilities, and optimistic about their future health. These findings suggest that nostalgia promotes a younger view of the self that may be beneficial for health.